Global Climate Change and Its Impact on Agriculture Sector in Pakistan - Awan, Abdul Ghafoor; Yaseen, Ghulam (American Journal of Trade and Policy, 2017)
Impact of global climate change on the agriculture sector of Pakistan is estimated in Pakistan. Agriculture is considered as the backbone of Pakistan economy because more 60% population is directly involved with this profession. Due to rapid industrialization the temperature level is increasing, which is harmful for agriculture crops and also for people. The objective of this research paper is to explore the impact of the global warming at agriculture sector of Pakistan and to measure climate impact on the agriculture sector in future. Times series dataset from 1974 to 2013 is used to analyze the impact. Agriculture value added annual growth rate is used as dependent variable. Carbon oxide emission, agriculture methane emission, agriculture nitrous oxide emission, greenhouse gas emission and population density are used as explanatory variables. Auto regressive distributed lag model is used as statistical technique to analyze the dataset. The result shows that the variables have significant impact on the agriculture sector of Pakistan. Auto regressive distributed lag model presents the existence of the short run and long run relationship between the dependent and independent variables. In a policy recommendation government try to reduce the warming through control on industrialization.